WORTSCHATZERINNERUNGSKARTE: MENGUASAI BAHASA MELALUI KOSA KATA - Rofi'ah Rofi'ah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study aimed to describe the use of Wortschatzerinnerungskarte as an instructional medium of teaching German as a foreign language and the results of its use in the classroom. The study was design to promote longer vocabulary retention to learners of German as a foreign language. This was a descriptive quatitative study that used quantitative data to support the analysis of qualitative data. The researcher was the main instrument of the study. The other instruments used were observation sheet, test and questionnaire. The result of the study revealed that the use of Wortschatzerinnerungskarte improved the student’s learning motivation. Moreover, this instructional medium can help the students remember the vocabulary better and boost up their learning performance